Empowerment of Carocok Port in Improving the Economy of the Koto XI Tarusan, West Sumatra - Johan Septian Putra (Kreativasi : Journal of Community Empowerment, 2022)
From the establishment of Carocok Port until the era of modernization in fishing from the fishermen, it provides proof that the people of Koto XI Tarusan District get their livelihood from the sea it has an economic impact on their respective families. The research objectives are to explain the socio-economic condition of the Koto XI Tarusan Sub-district, describe Carocok Port, and analyze the empowerment and management of the Carocok Port fisheries economy for the Koto XI Tarusan Sub-district Community. This research uses a qualitative descriptive approach in the form of a case study focusing on a particular unit. The results of the research in this article, namely: First, the community of Koto XI Tarusan Sub-district is located in Pesisir Selatan Regency with livelihoods from the sea. Most people are still categorized as poor. Second, the location of the port is very strategic and fantastic with natural beauty, safe from big waves, and recreational areas for tourists. Third, the empowerment and management of the Carocok Port fisheries economy are experiencing optimal utilization of marine and fisheries resources and continuity.